KONSTRUKSI NARASI HUMAN CAPITAL VS RELATIONAL CAPITAL SEBAGAI KOMUNIKASI STRATEGIS PERUSAHAAN RITEL PASCA PANDEMI - Umar Hamdan Nasution (Universitas Dharmawangsa, 2026)
The post-pandemic financial performance recovery of the retail sector demands reliable allocation management of working capital and intangible assets. This qualitative study aims to dissect, classify, and interpret the narrative construction of Human Capital (HC) versus Relational Capital (RC) in the Annual Reports of retail companies listed on the Indonesia Stock Exchange (IDX). Employing a descriptive-exploratory qualitative content analysis method without field interviews, this study examines the official secondary documents of three major retail issuers for the 2022–2024 period through a strategic financial management-based keyword coding matrix. The results indicate that corporations actively utilize non-financial disclosures as rhetorical communication tools to signal operational resilience to the market. The construction of HC narratives focuses on operating cost efficiency and front-line staff digital capacity adaptation. Meanwhile, RC narratives are constructed more aggressively through the articulation of customer loyalty programs and distribution partnership expansion. Comparatively, the Relational Capital text cluster significantly dominates the direction of financial management reporting compared to human capital. This dominance indicates the strategic priority of companies to secure cash flow retention and external market share capture as the primary cushion against financial risks during economic recovery. Keywords: Content Analysis, Financial Management, Intellectual Capital, Retail Companies, Strategic Communication